Implementation Of The Pancasila Student Profile Strengthening Project In Social Studies Learning - Enisa Intan Nuraini; Anita Lisdiana (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2026)
The implementation of the Pancasila Student Profile Strengthening Project (P5) at SMP Negeri 5 Metro shows variations in teachers’ levels of understanding and involvement, which affect the quality of the learning process. This study aims to examine the implementation of the P5 program in social studies learning and its impact on both the learning process and the development of students’ character. The research adopts a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the implementation of P5 is conducted through systematic stages, namely planning, implementation, and reflection. The impact of P5 is reflected in students’ improved understanding of social studies concepts through contextual project-based activities. In addition, the project fosters the development of cooperative character through group work, encourages a sense of responsibility in completing project tasks, and enhances students’ critical thinking skills through discussion and reflective activities. Overall, P5 contributes positively to strengthening social studies learning and developing students’ character in accordance with Pancasila values.